Microoxygraph Device for Biosensoristic Applications. (22nd December 2015) - Aloisi, A.; Tarentini, E.; Ferramosca, A.; Zara, V.; Rinaldi, R.
Abstract : Oxygen consumption rate (OCR) is a significant parameter helpful to determine in vitro respiratory efficiency of living cells. Oxygen is an excellent oxidant and its electrocatalytic reduction on a noble metal allows accurately detecting it. By means of microfabrication technologies, handy, low-cost, and disposable chip can be attained, minimizing working volumes and improving sensitivity and response time. In this respect, here is presented a microoxygraph device (MOD), based on Clark's electrode principle, displaying many advantageous features in comparison to other systems. This lab-on-chip platform is composed of a three-microelectrode detector equipped with a microgrooved electrochemical cell, sealed with a polymeric reaction chamber. Au working/counter electrodes and Ag/AgCl reference electrode were fabricated on a glass slide. A microchannel was realized by photoresist lift-off technique and a polydimethylsiloxane (PDMS) nanoporous film was integrated as oxygen permeable membrane (OPM) between the probe and the microreaction chamber. Electrochemical measurements showed good reproducibility and average response time, assessed by periodic injection and suction of a reducing agent. OCR measurements on 3T3 cells, subjected, in real time, to chemical stress on the respiratory chain, were able to show that this chip allows performing consistent metabolic analysis.